PENGARUH KEPATUHAN WAJIB PAJAK ORANG PRIBADI TERHADAP PENERIMAAN PAJAK DI KPP PRATAMA SURABAYA KREMBANGAN - ALFIAN, RAHMAD (Jurnal Akuntansi AKUNESA, 2013)
One of the most important state revenue is the tax sector. But the fact remains thatmany taxpayers do not have the awareness of taxation in the taxation obligations. Thepurpose of this study was to examine and analyze the influence of personal taxpayercompliance of tax revenue in the Tax Office Primary Surabaya Krembangan the period 2007-2010. The data of this study using secondary data, namely the number of personal taxpayer isregistered, the number of personal taxpayer who pays tax, and the amount of tax revenue inthe Tax Office Primary Surabaya Krembangan. Regression models are used in compliancewith the assumptions of classical test. Data analysis technique used was simple linearregression analysis techniques. Based on the analysis performed can be concluded that therewas no significant effect on the level of taxpayer compliance with tax revenues in the TaxOffice Primary Krembangan Surabaya Keywords: Tax Obligations, Taxpayer Compliance, Tax Revenues